ERRORS MADE BY IRAQI EFL UNDEGRAGUATE STUDENTS IN USING MANDATIVE SUBJUNCTIVES - AlMamoory, Salih Mahdi Adai; Watoot, Sebe Zeid (International Journal of Psychosocial Rehabilitation, 2020)
This paper is to analyze errors made by Iraqi EFL undergraduate students in using mandative subjunctive at the University of Babylon. Identifying and analyzing errors as well as finding out their causes that are crucial in foreign language learning. This case study focuses on analyzing forty five sheets to find out solutions to improve accuracy in language competence for the learners. The results show that the learners make different types of errors and they are not qualified enough as mandative as concerned. The error analysis contributes to raising awareness about the precise use of mandative subjunctive to improve learners' language ability.